2021
DOI: 10.1177/1086296x20986910
|View full text |Cite
|
Sign up to set email alerts
|

Accountability in Adult Basic Education: The Marginalization of Adults with Difficulty Reading

Abstract: Federal accountability policies requiring rapid, measurable outcomes have increasingly shaped the nature and type of public literacy services available to adults. However, little empirical research has explored the impact of accountability policies on program practice in adult basic education, and almost no research has focused on the effect on services for adults who have difficulty reading. This ethnographically grounded research article explores one publicly funded adult basic education program’s efforts to… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
9
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 12 publications
(9 citation statements)
references
References 34 publications
0
9
0
Order By: Relevance
“…Second, the authors emphasized that WIOA-mandated coordination between ABE providers and workforce development partners, including employers, could potentially increase access to services for some students (Bergson-Shilcock, 2019;Davidson, 2017;Green, 2020), but also requires ABE providers and students to prioritize employers' needs (Reder, 2020;Shin & Ging, 2019). Next, the authors criticized the new performance accountability system (McHugh & Doxsee, 2018;Pickard, 2016;Reder, 2020) and how it disincentivizes ABE providers from supporting adult learners who would benefit most from adult education (Pickard, 2021a(Pickard, , 2021b. Finally, the authors asserted that WIOA's prevailing focus on economic outcomes constricts adults' opportunities to achieve other lifewide goals such as civic engagement or family literacy (Belzer, 2017;Clymer et al, 2017;McHugh & Doxsee, 2018;Vanek, 2016;Vanek et al, 2020) and discourages providers from working toward educational equity (Yankwitt, 2020).…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…Second, the authors emphasized that WIOA-mandated coordination between ABE providers and workforce development partners, including employers, could potentially increase access to services for some students (Bergson-Shilcock, 2019;Davidson, 2017;Green, 2020), but also requires ABE providers and students to prioritize employers' needs (Reder, 2020;Shin & Ging, 2019). Next, the authors criticized the new performance accountability system (McHugh & Doxsee, 2018;Pickard, 2016;Reder, 2020) and how it disincentivizes ABE providers from supporting adult learners who would benefit most from adult education (Pickard, 2021a(Pickard, , 2021b. Finally, the authors asserted that WIOA's prevailing focus on economic outcomes constricts adults' opportunities to achieve other lifewide goals such as civic engagement or family literacy (Belzer, 2017;Clymer et al, 2017;McHugh & Doxsee, 2018;Vanek, 2016;Vanek et al, 2020) and discourages providers from working toward educational equity (Yankwitt, 2020).…”
Section: Discussionmentioning
confidence: 99%
“…The performance accountability system also influences ABE instruction. Authors documented how practitioners devote substantial time to testing and test preparation, in the case of English language learners in an IET, Certified Nursing Assistant program (Britton & Austin, 2020) and adult literacy classes (Pickard, 2021a(Pickard, , 2021b. Furthermore, Pickard (2021a) suggested that the emphasis on accountability has shifted professional development, likely influencing the types of instructional services that practitioners can provide.…”
Section: Heightened Yet Narrowed Accountabilitymentioning
confidence: 99%
See 1 more Smart Citation
“…This has meant that adult literacy programs, particularly those subsidized by government, are subject to increasing accountability requirements. Researchers in the United Kingdom (Tusting, 2009), United States (Pickard, 2021), and Australia (Osmond, 2021) all report the high volume of ‘form‐filling’ that is required by teachers to demonstrate that they are addressing curriculum outcomes. Moreover, the idea of curriculum as something negotiated around learner needs has shifted to an externally produced, standardized ‘product’ with a heavy focus on assessment.…”
Section: Literature Reviewmentioning
confidence: 99%
“…Consequently, reading and writing are related to further education and employment opportunities (de Beer et al, 2014;Hulme & Snowling, 2016). Students who struggle with reading and writing are at risk of marginalization (Pickard, 2021;World Literacy Foundation, 2012). With the knowledge that reading and writing are related to students' early oral language and language teaching (Castles et al, 2018), early education is essential in promoting language development for all young students.…”
Section: Introductionmentioning
confidence: 99%